Mesenchymal Wnt/β‐Catenin Signaling Controls Epithelial Stem Cell Homeostasis in Teeth by Inhibiting the Antiapoptotic Effect of Fgf10. (23rd April 2015) - Yang, Zheqiong; Balic, Anamaria; Michon, Frederic; Juuri, Emma; Thesleff, Irma
Abstract: Continuous growth of rodent incisors relies on epithelial stem cells (SCs) located in the SC niche called labial cervical loop (LaCL). Here, we found a population of apoptotic cells residing in a specific location of the LaCL in mouse incisor. Activated Caspase 3 and Caspase 9, expressed in this location colocalized in part with Lgr5 in putative SCs. The addition of Caspase inhibitors to incisors ex vivo resulted in concentration dependent thickening of LaCL. To examine the role of Wnt signaling in regulation of apoptosis, we exposed the LaCL of postnatal day 2 (P2) mouse incisor ex vivo to BIO, a known activator of Wnt/β‐catenin signaling. This resulted in marked thinning of LaCL as well as enhanced apoptosis. We found that Wnt/β‐catenin signaling was intensely induced by BIO in the mesenchyme surrounding the LaCL, but, unexpectedly, no β‐catenin activity was detected in the LaCL epithelium either before or after BIO treatment. We discovered that the expression of Fgf10, an essential growth factor for incisor epithelial SCs, was dramatically downregulated in the mesenchyme around BIO‐treated LaCL, and that exogenous Fgf10 could rescue the thinning of the LaCL caused by BIO. We conclude that the homeostasis of the epithelial SC population in the mouse incisor depends on a proper rate of apoptosis and that this apoptosis is controlled by signals from the mesenchyme surrounding the LaCL. Fgf10 is a key mesenchymal signal limiting apoptosis of incisor epithelial SCs and its expression is negatively regulated by Wnt/β‐catenin. Stem Cells 2015;33:1670–1681